2006
DOI: 10.1354/vp.43-6-971
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor, Basic Fibroblast Growth Factor, and Their Receptors (Flt-1, Flk-1, and Flg-1) in Canine Vascular Tumors

Abstract: Abstract. Expression of vascular endothelial growth factor (VEGF), its receptors (flt-1 and flk-1), and basic fibroblast growth factor (bFGF) in canine hemangiosarcoma (HSA) and hemangiomas was investigated by immunohistochemical analysis. In addition, expression of the mRNAs of VEGF, flt-1, flk-1, and flg-1 (a receptor for bFGF), was analyzed by reverse transcriptase polymerase chain reaction (RT-PCR) and in situ hybridization (ISH) with cRNA probes. VEGF, bFGF, flt-1, and flk-1 were immunohistochemically det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 30 publications
3
85
0
Order By: Relevance
“…However, all haemangioma and haemangiosarcoma (HSA) endothelial cells showed cytoplasmic reactivity to VEGF, as indicated by the large number of positively stained cells. Similar results were obtained by Yonemaru et al (21). They demonstrated that the percentage of cells showing VEGF expression was significantly higher in haemangisarcomas than in haemangiomas (P < 0.05), and the expression of VEGF and Flk-1 receptor may be related to the proliferation of haemangiosarcoma cells.…”
Section: Discussionsupporting
confidence: 88%
“…However, all haemangioma and haemangiosarcoma (HSA) endothelial cells showed cytoplasmic reactivity to VEGF, as indicated by the large number of positively stained cells. Similar results were obtained by Yonemaru et al (21). They demonstrated that the percentage of cells showing VEGF expression was significantly higher in haemangisarcomas than in haemangiomas (P < 0.05), and the expression of VEGF and Flk-1 receptor may be related to the proliferation of haemangiosarcoma cells.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the immunohistochemistry results presented here, other studies have shown that canine angiosarcomas express increased VEGF and VEGFR2 compared to haemangiomas, and also express increased VEGFR1 and bFGF [229]. These findings contrast with those from the immunohistochemistry analysis of the human vascular tumours.…”
Section: Canine Angiosarcomassupporting
confidence: 84%
“…Although flt-1 has less tyrosine kinase activity than flk-1, some reports have demonstrated that increased flt-1 correlates with that of VEGF and tumor grade [10]. Yonemaru et al [12] recently reported that VEGF and its receptors might be associated with the malignant proliferation of canine hemangiosarcoma. In addition, flt-1 plays an important role in the pulmonary metastasis of tumors [3].…”
mentioning
confidence: 99%